Effectiveness of supported living in relation to shared accommodation - Fisher, Karen; Parker, Sarah (UNSW Sydney, 2007)
The Disability Policy and Research Working Group has commissioned the UNSW Consortium to research the effectiveness of supported living in relation to shared accommodation to improve service delivery to people with disabilities. The research has two parts: improving access to housing and improving models for people with disabilities who require 24-hour support. The project is to build on the priority area of strengthening access to services, including housing. It will build on knowledge and research to increase access to housing and enable specialist disability services to respond to identified gaps. More information is needed on the range models for people with support needs. They also need to know the actual barriers and access gaps that people experience trying to access housing to facilitate other models eg social housing barriers. The research will inform future CSDTA opportunities.
SPRC Report 6/07